Hybrid small-diameter vascular grafts: Anti-expansion effect of electrospun poly ε-caprolactone on heparin-coated decellularized matrices. (January 2016) - Gong, Wenhui; Lei, Dong; Li, Sen; Huang, Peng; Qi, Quan; Sun, Yijun; Zhang, Yijie; Wang, Zhe; You, Zhengwei; Ye, Xiaofeng; Zhao, Qiang
Abstract: Small-diameter vascular grafts (SDVGs) (D < 6 mm) are increasingly needed in clinical settings for cardiovascular disease, including coronary artery and peripheral vascular pathologies. Vessels made from synthetic polymers have shortcomings such as thrombosis, intimal hyperplasia, calcification, chronic inflammation and no growth potential. Decellularized xenografts are commonly used as a tissue-engineering substitute for vascular reconstructive procedures. Although acellular allogeneic vascular grafts have good histocompatibility and antithrombotic properties, the decellularization process may damage the biomechanics and accelerate the elastin deformation and degradation, finally resulting in vascular graft expansion and even aneurysm formation. Here, to address these problems, we combine synthetic polymers with natural decellularized small-diameter vessels to fabricate hybrid tissue-engineered vascular grafts (HTEV). The donor aortic vessels were decellularized with a combination of different detergents and dehydrated under a vacuum freeze-drying process. Polycaprolactone (PCL) nanofibers were electrospun (ES) outside the acellular aortic vascular grafts to strengthen the decellularized matrix. The intimal surfaces of the hybrid small-diameter vascular grafts were coated with heparin before the allograft transplantation. Histopathology and scanning electron microscope revealed that the media of the decellularized vessels were severely injured. Mechanical testing of scaffolds showed that ES-PCL significantly enhanced the biomechanics of decellularized vessels. Vascular ultrasound and micro-CT angiography showed that all grafts after implantation in a rat model were satisfactorily patent for up to 6 weeks. ES-PCL successfully prevented the occurrence of vasodilation and aneurysm formation after transplantation and reduced the cell inflammatory infiltration. In conclusion, the HTEV with perfect histocompatibility and biomechanics provide a facile and useful technique for the development of SDVGs.